Research Progress on the Preparation, Physiological Activity and Action Mechanism of Plant Derived Bioactive Peptides - Sinan LI; Xi WANG; Yu AN; Jun YU; Kaiyuan XU; Jia WANG; Zhihui ZHANG; Meng WANG; Aqin WANG; Ying WANG; Lu ZHANG (Shipin gongye ke-ji)
In recent years, with the increasing demand of consumers for functional foods and formula foods for special medical purposes, bioactive peptides (BAPs) with potential edible and medicinal value have received extensive attention. Plant-derived BAPs come from a wide range of sources, are safe and non-toxic. At present, a large number of plant-derived BAPs have been identified by isolation and purification. In addition to rich nutritional value, they also have various physiological activities such as antioxidant, hypoglycemic, hypertensive and antibacterial. In this paper, the preparation methods, physiological activity and action mechanism of plant-derived BAPs are reviewed, and the existing shortcomings and future development direction are discussed, in order to provide beneficial theoretical support for further research and industrial application of plant-derived BAPs in the field of food and medicine.